ANALISIS PENYEBAB DAN DAMPAK PERNIKAHAN DINI PADA NOVEL DUA GARIS BIRU KARYA LUCIA PRIANDARINI - Wulan Andari; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The problems in this study are 1) how the representation of the causes of early marriage in the novel Dua Garis Biru by Lucia Priandarini 2) how the representation of the impact of early marriage that occurs in the novel Dua Garis Biru by Lucia Priandarini. This study aims to 1) describe the representation of the causes of early marriage in the novel Dua Garis Biru by Lucia Priandarini and 2) describe the representation of the impact of early marriage that occurs in the novel Dua Garis Biru by Lucia Priandarini. This research uses a qualitative approach method, with the type of research, namely library research, which produces descriptive data in the form of words that are analyzed and observed. The data is taken from quotations in the novel Dua Garis Biru by Lucia Priandarini. From the results of the study, researchers found that the causes of early marriage can be caused by internal factors such as education, precociousness, and pregnancy before marriage. And the external factor is caused by a bad environment. Researchers also found the impact of early marriage from various aspects such as psychological, social, biological health, economic, and educational.